Cognitive Function in Adolescents and Young Adults With Youth-Onset Type 1 Versus Type 2 Diabetes: The SEARCH for Diabetes in Youth Study - Shapiro, Allison L.B.; Dabelea, Dana; Stafford, Jeanette M.; D’Agostino, Ralph; Pihoker, Catherine; Liese, Angela D.; Shah, Amy S.; Bellatorre, Anna; Lawrence, Jean M.; Henkin, Leora; Saydah, Sharon; Wilkening, Greta (Diabetes care, 2021)
Poor cognition has been observed in children and adolescents with youth-onset type 1 (T1D) and type 2 diabetes (T2D) compared with control subjects without diabetes. Differences in cognition between youth-onset T1D and T2D, however, are not known. Thus, using data from SEARCH for Diabetes in Youth, a multicenter, observational cohort study, we tested the association between diabetes type and cognitive function in adolescents and young adults with T1D ( = 1,095) or T2D ( = 285). Cognition was assessed via the National Institutes of Health Toolbox Cognition Battery, and age-corrected composite Fluid Cognition scores were used as the primary outcome. Confounder-adjusted linear regression models were run. Model 1 included diabetes type and clinical site. Model 2 additionally included sex, race/ethnicity, waist-to-height ratio, diabetes duration, depressive symptoms, glycemic control, any hypoglycemic episode in the past year, parental education, and household income. Model 3 additionally included the Picture Vocabulary score, a measure of receptive language and crystallized cognition. Having T2D was significantly associated with lower fluid cognitive scores before adjustment for confounders (model 1; < 0.001). This association was attenuated to nonsignificance with the addition of a priori confounders (model 2; = 0.06) and Picture Vocabulary scores (model 3; = 0.49). Receptive language, waist-to-height ratio, and depressive symptoms remained significant in the final model ( < 0.01 for all, respectively). These data suggest that while youth with T2D have worse fluid cognition than youth with T1D, these differences are accounted for by differences in crystallized cognition (receptive language), central adiposity, and mental health. These potentially modifiable factors are also independently associated with fluid cognitive health, regardless of diabetes type. Future studies of cognitive health in people with youth-onset diabetes should focus on investigating these significant factors.